(untitled) (Swiss Medical Weekly, 2019)
BACKGROUND AND AIMS Accurate diagnosis and staging of non-alcoholic fatty liver disease are essential for the management of this disorder. Controlled attenuation parameter (CAP) has been suggested as a new noninvasive measurement made during transient elastography to assess liver steatosis. The aim of this study was to evaluate CAP as a diagnostic tool for identifying the presence and degree of hepatic steatosis in consecutive patients in an outpatient liver unit of a tertiary centre. METHODS Between March 2015 and August 2016, all patients who underwent liver biopsy underwent liver stiffness measurement with simultaneous CAP determination using the FibroScan® M or XL probe. Steatosis, inflammatory activity and fibrosis were assessed using the histological SAF scoring system. In addition, fibrosis was scored according to the METAVIR system, and body mass index (BMI) and the underlying liver disease were also recorded. RESULTS 224 patients were included in the analysis; 146 (65.2%) were male. Steatosis grades were distributed as follows: S0 n = 85 (37.9%), S1 n = 82 (36.6%), S2 n = 33 (14.7%), S3 n = 24 (10.7%). Mean BMI was 26.8 kg/m2, for the S0 group 24.9 kg/m2, S1 26.5 kg/m2, S2 27.3 kg/m2 and S3 32.5 kg/m2. The CAP differed significantly between steatosis groups S0 to S3. The area under receiver operating characteristics curve for S0 vs S1–S3 was 0.78, for S0/1 vs S2/3 0.83 and for S0–2 vs S3 0.82. Calculated cut-off values were 258.5 dB/m for S0 vs S1–3, 282.5 dB/m for S0/1 vs S2/3 and 307.5 dB/m for S0–2 vs S3. CONCLUSIONS CAP values are strongly associated with the degree of steatosis irrespective of the underlying liver disease. Integrating CAP measurements in the standard work-up may identify patients with NAFLD.